Demons in Early Judaism and Christianity : Characters and Characteristics - Lössl, Josef,; Patmore, Hector M., (Ancient Judaism and Early Christianity ;, 2022)
This volume sheds light on how Jews and Christians in Antiquity understood the nature and characteristics of demons. The contributions cover a wide range of corpora and explore aspects of continuity and change as ideas flowed between groups and cultures.